2017
DOI: 10.1038/labinvest.2017.61
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial fibrosis induced by suppressed STAT3 expression mediated by signaling involving the TGF-β1/ALK5/Smad pathway

Abstract: During systemic inflammatory pathologies, mediators of inflammation circulate in the bloodstream and interact with endothelial cells (ECs), resulting in endothelial dysfunction that maintains and enhances the pathological condition. Inflammatory mediators change the protein expression profile of ECs, which become activated fibroblasts via endothelial-to-mesenchymal transition. This process is characterized by downregulated endothelial proteins and strongly upregulated fibrotic-specific genes and extracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…Endotoxininduced TGF-β isoform generation requires binding the TGF-β receptor type II (TβRII), which recruits TβRI or activin receptor-like kinase 5 (ALK5). Subsequently, ALK5 phosphorylates smad-2/3, which then binds smad-4 to regulate target gene transcription and promote fibrosis [25,32,34,35]. Thus, endotoxin-induced endothelial fibrosis is completely dependent on TGF-β secretion and ALK5 activation.…”
Section: Introductionmentioning
confidence: 99%
“…Endotoxininduced TGF-β isoform generation requires binding the TGF-β receptor type II (TβRII), which recruits TβRI or activin receptor-like kinase 5 (ALK5). Subsequently, ALK5 phosphorylates smad-2/3, which then binds smad-4 to regulate target gene transcription and promote fibrosis [25,32,34,35]. Thus, endotoxin-induced endothelial fibrosis is completely dependent on TGF-β secretion and ALK5 activation.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from JunB, transcription factor STAT3 has been shown to be involved in the positive regulation of ITGB6 basic transcription in OSCC cells, prostate, and breast epithelial cells . However, recent study presented that STAT3 signaling decreases TGF‐β1‐induced responses . We speculate that STAT3 may not be required for TGF‐β1‐induced ITGB6 transcription.…”
Section: Discussionmentioning
confidence: 77%
“…In turn, HPT and STAT3 interaction signaling is involved in the development of fibrosis and in the regulation of fibroblast senescence [14][15][16] . Interestingly, it has been demonstrated that the inhibition and activation of STAT3 are both related to the fibrosis onset following the cross-talk between STAT3 and TGF-β signaling, that is organ and tissue-dependent 17 . HPT could also be induced by the interaction of FGFR and VEGFR with CREB-binding protein (CBP), which is involved in cell growth, transformation and development and also shows histone acetyltransferase activity 18 .…”
Section: Discussionmentioning
confidence: 99%
“…5). The proteins of Group B (light blue bars) were associated with "liver regeneration" and "descending colon inflammation" (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Proteomic Analysis Of Sera From Ipf Patients Before and Aftementioning
confidence: 99%